Práctica de enseñanza de lenguaje en educación general básica, análisis de caso en primer año en la UECIB Misión Andina del cantón Pedro Moncayo. - Cabascango Cuascota, Verónica Alexandra (2016)
This qualification work was developed with the purpose to promote the development of the practice of teaching in the "Andean mission" UECIB, in the first year in the area of language. Which raise awareness in teaching good teaching practice which must be continuous and transformative which can only be reached questioning the practice. In the institution is unknown is the practice of teaching of language do not exist any document in which positive and negative aspects can occur causing a reflection on the subject. In the institution is unknown is the practice of teaching of language do not there is no document in which you can verify positive and negative aspects that provoke reflection and if the case warrants a change to improve the professional performance of the teacher. To do this use the qualitative method which allows us to describe the development of the teaching-learning process of the teacher in charge, by means of a participatory observation in the classroom, collecting information through a field journal and use of tokens of observation. The results of observation to the teacher's first year is: his teaching practice is guided by the curriculum of basic General education, and modified according to the way as she plans, evaluates, interacts, according to its principles and concepts of knowledge. To analyze the case presented was the selection of sources related to the topic and then check with what was observed.